Carrier ethernet : architecture, services, OAM, interworking - Toy, Mehmet (Wiley series on information and communications technologies., 2011)
This book provides a comprehensive understanding of current and debated future networking technologies. It gives insight into building end-to-end networks and services with Carrier Ethernet, PBT, MPLS-TP, and VPLS while also shedding light on the pros and cons of these technologies for service providers and enterprise network owners. Focusing on layer-2 networking and services, Networks and Services covers: The basics of Ethernet such as protocol stack, bridges, switches, and hubsKey techniques that are being used in building carrier-class Carrier Ethernet n.